2023
DOI: 10.2147/oajc.s407547
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenology of Induced Abortion in Northern Uganda Among HIV-Positive Women Following an Unintended Pregnancy

Abstract: Background More than half of pregnancies in Uganda are unintended, and nearly a third of these end in abortion. However, little research has focused on women living with HIV’s subjective experiences following induced abortion. We explored how women living with HIV subjectively experience induced abortions in health facilities in Lira District, Uganda. Materials and Methods This was a descriptive-phenomenological study between October and November 2022. The study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…The perception of abortion care is influenced by the individual’s attitude towards it. Women decide abortion is necessary due to financial constraints, unplanned pregnancy, and complicated social networks [ 98 ]. They may desire to keep their decision to have an abortion private, but that can lead to unsafe abortions and late care-seeking [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of abortion care is influenced by the individual’s attitude towards it. Women decide abortion is necessary due to financial constraints, unplanned pregnancy, and complicated social networks [ 98 ]. They may desire to keep their decision to have an abortion private, but that can lead to unsafe abortions and late care-seeking [ 99 ].…”
Section: Resultsmentioning
confidence: 99%
“…Women often consult many people in their community before deciding on how to access abortion services [ 102 ]. Kabunga et al [ 98 ] found that women who have an abortion experience a loss of family support and internalized perceived stigma.…”
Section: Resultsmentioning
confidence: 99%
“…Various factors associated with delayed ANC attendance have been unearthed in low-resource countries. These include unplanned and unconsented pregnancy, increased distance to a health facility, food insecurity, competing demands on family resources, long travel and waiting times, the number of health workers present at the facility and recommendations from village health teams (VHTs) for pregnant mothers to visit health centres to confirm pregnancies 9 10. These factors have been associated with first ANC attendance after 12 weeks of pregnancy among pregnant women 8 11 12.…”
Section: Introductionmentioning
confidence: 99%